Accuracy of algorithms to predict accessory pathway location in children with Wolff–Parkinson–White syndrome. Issue 3 (13th September 2011) - Wren, Christopher; Vogel, Melanie; Lord, Stephen; Abrams, Dominic; Bourke, John; Rees, Philip; Rosenthal, Eric
Abstract : Objective: The aim of this study was to examine the accuracy in predicting pathway location in children with Wolff–Parkinson–White syndrome for each of seven published algorithms. Patients and interventions: ECGs from 100 consecutive children with Wolff–Parkinson–White syndrome undergoing electrophysiological study were analysed by six investigators using seven published algorithms, six of which had been developed in adult patients. Main outcome measures: Accuracy and concordance of predictions were adjusted for the number of pathway locations. Results: Accessory pathways were left-sided in 49, septal in 20 and right-sided in 31 children. Overall accuracy of prediction was 30–49% for the exact location and 61–68% including adjacent locations. Concordance between investigators varied between 41% and 86%. No algorithm was better at predicting septal pathways (accuracy 5–35%, improving to 40–78% including adjacent locations), but one was significantly worse. Predictive accuracy was 24–53% for the exact location of right-sided pathways (50–71% including adjacent locations) and 32–55% for the exact location of left-sided pathways (58–73% including adjacent locations). Conclusions: All algorithms were less accurate in our hands than in other authors' own assessment. None performed well in identifying midseptal or right anteroseptal accessory pathway locations.